Urbanization on the Ottoman borders: small towns in the south-west serhad from the 16th to the 18th century - Jurin Starčević, Kornelija (Array, 2014)
Due to great geostrategic significance the area was organized as a military frontier of the sancaks of Klis, Krka, Bihać and partly Herzegovina in eyalet of Bosnia. In Ottoman sources, particularly in mühimme defteris this part of the frontier is often called “the end of frontier” or “the edge of frontier” (intiha-yı serhad). There existed a specific patterns of urban evolution because all towns gradually developed from the military strongholds. Even though urbanization of the frontier during the 16th and 17th centuries was limited, there is no doubt that certain Ottoman forts outgrew military frames and gained stronger civilian i.e. central functions. The whole south-west of the Bosnian eyalet eventually became criss-crossed by small towns with the population of several thousand which emerged from forts. The main subject of research of this paper are precisely such towns, towns to which the war represented a factor of urban development and which developed out of too great fear on south-western borders.